Combustion Characteristics Of A Swirl Combustor Operating On Kerosene Vegetable Cooking Oil (Vco) Fuel Blends - Sulaiman, Mohammad Shah Affandi (Universiti Sains Malaysia, 2019)
This research explores the combustion characteristics of a swirl combustor operating on KVCO fuel blends.The aim of this experiment is to study the performance and combustion characteristics of porous medium combustion using kerosene and vegetable cooking oil (VCO) as fuel blends. The swirl combustion is formed from the tangential air inlet that prevents heat loss in the chamber. The characteristics of the fuel were analyzed in terms of the performance and the temperature generated as well as the flow of the flame inside the combustor during the combustion. The experiment consists of two parts; using single air inlet ports and dual air inlet ports. The air flow rate was varied from 2 to 10 LPM and the fuel flow rate was fixed 0.01LPM during the experiment. Four fuel blends have experimented; 100% kerosene, 90/10% KVCO, 75/25% KVCO and 50/50% KVCO. Results show that both findings depicted the highest temperature recorded with 100 kerosene using two air inlet ports which is 815.3K and the equivalence ratio is close to stoichiometry. It shows that the swirling air helped in reducing the heat loss in the combustion process. The equivalence ratio is inversely proportional to the temperature. In addition, the mixture of fuel blends did not improve the combustion process due to the content of the vegetable cooking oil.